2005
DOI: 10.1136/vr.156.18.565
|View full text |Cite
|
Sign up to set email alerts
|

Controlled clinical trial of the effect of a homoeopathic nosode on the somatic cell counts in the milk of clinically normal dairy cows

Abstract: Cows in a 250-cow Holstein-Friesian herd were allocated at random to be treated with either a homoeopathic nosode or a negative control, both treatments being applied by means of an aerosol spray to the vulval mucous membranes. A total of six treatments were given over a period of three days and milk samples were taken for the determination of somatic cell counts (SCC) on days -3, 3, 7, 9, 14, 21 and 28. Individuals applying the treatments or carrying out the SCC determination were unaware of which animals wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 7 publications
(2 reference statements)
0
16
0
2
Order By: Relevance
“…Results of a recent study in mild to moderate clinical mastitis indicate that cows treated with homeopathy showed significantly higher SCC that those treated with antibiotics (Werner et al, 2010). When efficiency of homeopathy is compared with a placebo in cows suffering subclinical mastitis, Kiarazm et al (2011) found a significant decrease of the SCC and a reduction of the incidence of the disease in the group receiving homeopathy, even though Holmes et al (2005) did not find any significant effect of the treatment.…”
Section: Discussionmentioning
confidence: 96%
“…Results of a recent study in mild to moderate clinical mastitis indicate that cows treated with homeopathy showed significantly higher SCC that those treated with antibiotics (Werner et al, 2010). When efficiency of homeopathy is compared with a placebo in cows suffering subclinical mastitis, Kiarazm et al (2011) found a significant decrease of the SCC and a reduction of the incidence of the disease in the group receiving homeopathy, even though Holmes et al (2005) did not find any significant effect of the treatment.…”
Section: Discussionmentioning
confidence: 96%
“…The ability of a commercially available homeopathic nosode to influence SCC was evaluated in 152 Holstein-Friesian cows located in a single commercial dairy herd in the United Kingdom (Holmes et al, 2005). The nosode or a control solution was administered topically on the mucous membranes of the vulva twice daily for 3 consecutive days.…”
Section: Homeopathymentioning
confidence: 99%
“…Data presented include: medical condition, species, nature of the homeopathic intervention, and trial setting. The tabulation also includes details of the RCT's source of funding, together with the associated freedom from vested interest: only one trial (Holmes and others 2005) was deemed to be clearly free of such vested interest.…”
Section: Resultsmentioning
confidence: 99%
“…The direction of effect was towards homeopathy in each of the six trials from which data could be extracted. The seventh trial in this category (Holmes and others 2005) contained logarithmic data. Due to the diversity of medical conditions, species and types of homeopathic intervention displayed in these six trials, and the fact that analysis was limited to data from trials at low/unclear risk of bias, it was not considered appropriate to carry out meta-analysis on disease-specific treatment or prophylaxis.…”
Section: Resultsmentioning
confidence: 99%